2000
DOI: 10.1038/sj.cdd.4400744
|View full text |Cite
|
Sign up to set email alerts
|

Activation of PKC is sufficient to induce an apoptotic program in salivary gland acinar cells

Abstract: Accumulating evidence suggests that specific isoforms of PKC may function to promote apoptosis. We show here that activation of the conventional and novel isoforms of PKC with 12-O-tetradecanoyl phorbol-13-ester (TPA) induces apoptosis in salivary acinar cells as indicated by DNA fragmentation and activation of caspase-3. TPA-induced DNA fragmentation, caspase-3 activation, and morphologic indicators of apoptosis, can be enhanced by pretreatment of cells with the calpain inhibitor, calpeptin, prior to the addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
1
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(68 citation statements)
references
References 54 publications
(59 reference statements)
4
62
1
1
Order By: Relevance
“…The JNK pathway played a major role in the apoptotic effect of PKCyNuc because inhibition of JNK significantly decreased the apoptotic effect of the PKCy-Nuc. JNK has been implicated in the regulation of cell apoptosis in response to various stimuli (51,52) and has been shown to act downstream of PKCy (16,51,53,54). A role for the nuclear PKCy in the activation of JNK is further supported by recent studies that showed that the nuclear translocation of PKCy by etoposide preceded the activation of JNK in salivary gland acinar cells (30,53).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The JNK pathway played a major role in the apoptotic effect of PKCyNuc because inhibition of JNK significantly decreased the apoptotic effect of the PKCy-Nuc. JNK has been implicated in the regulation of cell apoptosis in response to various stimuli (51,52) and has been shown to act downstream of PKCy (16,51,53,54). A role for the nuclear PKCy in the activation of JNK is further supported by recent studies that showed that the nuclear translocation of PKCy by etoposide preceded the activation of JNK in salivary gland acinar cells (30,53).…”
Section: Discussionmentioning
confidence: 50%
“…JNK has been implicated in the regulation of cell apoptosis in response to various stimuli (51,52) and has been shown to act downstream of PKCy (16,51,53,54). A role for the nuclear PKCy in the activation of JNK is further supported by recent studies that showed that the nuclear translocation of PKCy by etoposide preceded the activation of JNK in salivary gland acinar cells (30,53). Thus, JNK may represent another nuclear PKCy substrate in addition to the already well-characterized substrates, p73 (19) and DNA-PK (20).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that activation of PKC by phorbol ester is sufficient to induce an apoptotic program in parotid salivary epithelial cells 15 and that PKCd is essential for genotoxin-induced cell death in these cells. 13,16 Here, we demonstrate that inhibition of endogenous PKCa induces an apoptotic program in salivary epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] Serine/threonine protein kinases are also known to regulate apoptosis, including the phosphoinositide 3-kinase/AKT pathway, 8,9 members of the mitogen-activated protein kinase family (MAPKs), [10][11][12] and the protein kinase C (PKC) pathway. [13][14][15][16][17] The PKC family consists of 11 isoforms, with individual isoforms exhibiting varying substrate specificity, as well as differences in their subcellular localization and response to specific stimuli. 18,19 This argues that specific isoforms of PKC play unique roles in transducing cell signals.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 PKC activated by TPA inhibits apoptotic responses to TNFα, 6,7 chemotherapy, 8 growth factor withdrawal 9 and radiation. 10 However, in some cell types TPA-activated PKC induces, rather than attenuates apoptosis, such as in EBV-infected Burkitt Lymphoma cells, 11 immature thymocytes, 12 salivary gland acinar cells, 13 human MCF-7 breast cancer cells 14 and LNCaP cells. 1,15 Using genetic and pharmacologic inhibition of specific PKC isozymes Garcia-Bermejo et al, 2 showed that both PKCα and PKCδ mediate TPA-induced apoptosis in LNCaP cells, although the mechanism of action remains undefined.…”
Section: Introductionmentioning
confidence: 99%